Ancient archaeological finds related to weaving in Azerbaijan - Museibli, Najaf (Revista Arheologică, 2026)
As a result of archaeological excavations conducted in Azerbaijan, numerous finds related to the weaving art have been discovered in monuments dating from the Neolithic to all subsequent periods. These are tools with piercing functions such as spindle whorls, needles, awls and pins made of clay and bone, and rarely from stone. In the Bronze Age, piercing tools were also made of metal. Traces of fabrics woven in various ways on ceramic products dating from the Neolithic, Chalcolithic and Bronze Ages are indicators of the widespread development of this art form in ancient Azerbaijan. Thus, the “bagging method” used in the production of pottery indicates that the bag, which is a woven product, was also applied in the field of pottery. At the same time, direct remains of fabric were also discovered during the excavations. Although the remains of fabric discovered in grave monuments are very poorly preserved, they indicate that weaving was one of the main craft forms in the region. Some examples of clothing found among the petroglyphs are also a certain source of information about ancient weaving.